Motivation of Santri in Memorizing the Holy Qur'an through Murojaah Activities: Study in Roudlothul Qur'an PPAI Complex - Nuha, Muhammad Ulin (Interdisciplinary Journal of Social Science and Education (IJSSE), 2023)
Tahfidz is an activity of memorizing the Qur'an. This Qur'an memorization activity is often found in Islamic educational institutions such as Pondok Pesantren, TPQ, Madin to schools/madrasas. This study aims to explore the impact of murojaah activities on motivation in memorizing the Qur'an. Murojaah is the practice of repeating the Qur'an regularly to strengthen students' memorization and understanding. This study used a qualitative approach by collecting data through in-depth interviews with a group of santri who were active in murojaah activities in a pesantren. The results of this study show that murojaah activities have a significant positive impact on motivation to memorize the Qur'an. The santri reported that through murojaah, they felt increased confidence, a stronger desire to memorize, and a deep intrinsic drive to gain blessings from the Qur'an. In addition, santri also revealed that murojaah helped them to maintain and improve their previously learned memorization. This study provides a better understanding of the positive impact of murojaah activities on motivation to memorize the Qur'an. The implication of this study is that the use of murojaah in the Qur'an memorization program can be an effective strategy to motivate students to memorize the Qur'an. Pesantren and teachers can consider integrating murojaah in a structured and sustainable manner in their tahfidz curriculum to increase santri learning motivation and achievement in memorizing the Qur'an.